WHATSAPP VOICE CHAT (WVC) AS AN EFL ONLINE LEARNING MEDIA - Adia Budjana; Achmad Anang Darmawan; Lina Aris Ficayuma (STKIP Al Hikmah Surabaya, 2023)
In recent years, researcher interested in mobile-assisted language learning (MALL) for online learning of English as a foreign language (EFL). In the current era of digitalization, access to information and materials can be easily found in cyberspace, either by accessing a page or by using an application. With these advances in technology, can be used as a tool to facilitate the educational process. The Ministry of Education and Culture is aware of the current needs,because by utilizing technology it can reach and distribute broad policies, as well as optimize the implementation of the Merdeka curriculum. As a teacher, this is a challenge in itself to bring students to learning transformation, where the teacher acts as a facilitator to encourage the learning process.